Pengaruh Pemberian Kompres Hangat Terhadap Penurunan Nyeri Punggung Pada Kehamilan Trimester III - Resti Setyaningsih; Dahlia Arief Rantauni; Septi Tri Aksari; Norif Didik Nur Imanah (STIKes Ibnu Sina Ajibarang, 2025)
Pregnancy is a physiological process that brings about various physical changes, one of which is lower back pain, commonly occurring in the third trimester. Hormonal changes, weight gain, and a shift in the body’s center of gravity are the primary factors contributing to this complaint. Back pain can interfere with daily activities and reduce the quality of life for pregnant women. One non-pharmacological method that can be used to alleviate pain is warm compress therapy. This study aims to evaluate the effectiveness of warm compresses in reducing the intensity of back pain in third-trimester pregnant women. The method used is a case study with a descriptive observational approach and the 7-step Varney management (SOAP). The subject of the study is Mrs. A, at 39 weeks of pregnancy, who received regular warm compress therapy. The results showed a significant decrease in pain, from an average pain scale of 7 to 4 after the intervention. Warm compresses provide muscle relaxation, increase blood circulation, and reduce muscle tension due to ischemia. Based on the gate control theory, warm compresses suppress pain perception in the brain and provide comfort for pregnant women.